High Incidence of Gestational Trophoblastic Disease in a Third-Level University-Hospital, Italy: A Retrospective Cohort Study - Capobianco, Giampiero; Tinacci, Elettra; Saderi, Laura; Dessole, Francesco; Petrillo, Marco; Madonia, Massimo; Virdis, Giuseppe; Olivari, Alessandro; Santeufemia, Davide Adriano; Cossu, Antonio; Dessole, Salvatore; Sotgiu, Giovanni; et al. (Frontiers in Oncology, 2021)
Introduction to assess incidence, prognosis and obstetric outcome of patients treated for gestational trophoblastic disease GTD in a twenty-year period. Incidence, prognosis and obstetric outcome of gestational throphoblastic disease Methods retrospective study. Results Fifty-four cases of GTD: 46 (85.18%) cases of Hydatidiform mole (HM); 8 cases of Persistent Gestational Trophoblastic Neoplasia (GTN) (14.81%): 6/8 cases (75%) GTN not metastatic; 2/8 cases (25%) GTN metastatic. In both cases, the metastases occurred in the lungs. In 3 out of 8 GTN cases (37.5%) a histological picture of choriocarcinoma emerged. The incidence of GTD cases treated from 2000 to 2020 was 1.8 cases per 1000 deliveries and 1.3 cases per 1000 pregnancies. Of the 54 patients, 30 (55.56%) presented showed normal serum hCG levels without the need for chemotherapy. On the other hand, 24 patients (44.44%) developed a persistent trophoblastic disease and underwent adjuvant therapy. The negative prognostic factors that affected the risk of persistence of GTD were: serum hCG levels at diagnosis > 100,000 mUI/ml; characteristic “snow storm” finding at the ultrasound diagnosis; a slow regression of serum hCG levels during follow-up; the persistence of high serum hCG levels (especially if > 1000 mUI/ml one month after suction curettage) that was the main risk factor for resistance to first-line chemotherapy. There were 10 pregnancies in total following treatment. Patients’ survival in our study was 100%. Discussion Although GTD is a rare disease, its incidence was 1.3 cases per 1,000 pregnancies in Sardinia, Italy, higher if compared with mean national and worldwide incidence.